Photocatalytic activity of TiO2 thin films deposited by cathodic arc - Kleiman, Ariel Javier (2011)
In this work, the photocatalytic activity and the kinetic behavior of anatase TiO2 films deposited by cathodic arc (CA films) on glass substrates is reported and compared with TiO2 Degussa P-25 films obtained by dip-coating immersion. The mass density of films, determined by X-ray reflectometry, allowed the assessment of the porosity of samples. The activity was evaluated from the efficiency to reduce Cr(VI) in the presence of EDTA. Although the response of CA films resulted lower compared with that of P-25 films (a fact associated to a lower porosity), adhesion properties of the new materials were much better. CA film photoactivity improved by increasing the coating thickness. These photocatalysts, whose preparation is simple and affordable, are very promising to be used as immobilized materials in photoreactors for the treatment of pollutants not only in the gas phase but also in aqueous systems.